Letter (copy) : Spanish refugees in France - Citrine, Walter, 1887-1983
026-0089-001 International. WMC/WJB/EK/1198. 25th May, 1939. Senor Jose I. de Lizaso, Basque Delegation, 14, Eccleston Square, London, S.W.1. Letter to A.E.U. See file 910.4181 Dear Senor Lizaso, SPANISH REFUGEES IN FRANCE. We duly received your letter of the 22nd May, in which you enquire as to the possible employment in this country of the skilled Spanish workers now in concentration camps In France. Before sending you a reply, I thought that the best way to get to know whether your proposal could be carried out would be to consult the members of the General Council who happened to be meeting this week. I duly laid the matter before them. It was pointed out that the policy of the British Government is opposed to the employment of other than British subjects in their armament workshops. However, the Council are very anxious to help you, and they have given me definite instructions to approach the Union concerned and to ask its Executive Council whether they think occupation could be found for the Spanish workers in private undertakings. As soon as I receive the views of this organisation on the matter I will write to you again. Yours faithfully, General Secretary. 292/946/26/89